EXCHANGE RATE FLUCTUATION AND NIGERIA’S ECONOMIC GROWTH (Journal of Contemporary Issues in Accounting, 2021)
The study investigates the effect of exchange rate fluctuation on economic growth of Nigeria: 1996 – 2016. The research adopted Rudi Dornbusch Exchange rate overshooting model as the main theoretical framework. The study employed multiple regression analysis with Ordinary Least Square (OLS) econometric technique to examine the effect of exchange rate fluctuation on the economic growth in Nigeria. The result showed that exchange rate has significant positive effect on economic growth in Nigeria. It therefore suggests strict foreign control policies in order to determine appropriate exchange rate value in Nigeria.
Keywords: Economic growth; exchange rate; exchange rate appreciation; exchange rate depreciation